Simulation of Piezoelectric Transducer for Detecting Water Leak in Polyethylene Pipelines - Mohd Puad, Ahmad Adzim; Mohd Muji, Siti Zarina; Roslee, Nuriffat; Abdul Kadir, Herdawatie; Isa, Khalid; Joret, Ariffuddin; Aminuddin, Nuramin Fitri (Evolution in Electrical and Electronic Engineering, 2020)
Pipeline leakage is known to cause severe economic losses and environmental harms. Conventionally, the pipeline monitoring methods, such as investigation (visual), GPR, or correlation have slow leakage responses and require a large human workforce. The objective of this work is to implement piezoelectric sensors for detecting pipeline leakage response by using acoustic pressure and sound pressure principles. Two types of pipe with diameter 50mm were used in the work, namely polyethylene pipe with and without aluminium coating. In this project, the bubble is used as the leakage indicator where several pipes with diameters of 30mm, 20 mm and 10 mm are used to mimic the bubble. A piezoelectric transmitter is then used to produce sound waves and allowing the shear waves to propagate throughout the pipeline vessel. A receiver piezoelectric then converts the motion of shear waves into electrical signals. The shear waves obtained seen to resulted within three values of frequencies, which are 3 kHz, 6 kHz, and 9 kHz. The obtained results are then analyzed using the COMSOL MultiphysicsTM software installed on the computer. From the findings, it can be concluded that the acoustic pressure field is affected by the size of the bubble and the appearing water bubbles in the pipe can be used to detect the leakage. It also comfirms that the polyethylene pipe with aluminium coating is more suitable to be used along with a piezoelectric transducer compared to polyethylene pipe without aluminium coating.